DETERMINANTS OF CAPITAL STRUCTURE: EVIDENCE FROM FOOD AND BEVERAGE COMPANIES IN INDONESIA - Kusumajaya, Clarissa Eunike; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2025)
Capital structure holds a significant role in determining the companies’ financial stability. Managing the combination of debt and equity as funding sources is a strategic decision that management must make in ensuring that the company's financing is used efficiently, supporting operational growth and maintaining financial stability. This study aims to determine the effect of profitability, liquidity, asset structure, and firm size on the capital structure of a company. Observations in this study consisted of 108 data derived from 36 food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2023. The sample selection technique applied was purposive sampling. Data processing in this study was carried out using EViews 13 software. The hypothesis testing method applied in the study was the multiple linear regression model. Estimation of multiple linear regression models suitable was the Fixed Effect Model (FEM). Capital structure in this study was measured by the Debt on Equity (DER) parameter. The data, after processed, indicated that profitability and liquidity negatively and significantly affect the capital structure, company size positively and significantly affect the capital structure, wile asset structure had no impact on the capital structure. The findings of this study provide insights into how internal factors can affect the decisions of capital structure and the financial stability of the firm. Management can use this result to optimize financing policy, while investors can use this as a guide in assessing the company's capital policy.